Pengaruh Size, Growth, dan Kondisi Keuangan Perusahaan Terhadap Capital Structure Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI - Masril, Masril; Ariesta, Nadhya Theressiana; Jefriyanto, Jefriyanto; admin, admin (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine the effect of company size, company growth and financial condition on capital structure in consumer goods industrial sector companies listed on the Indonesia Stock Exchange 2017-2019. The samples in this study were 32 companies with research data for 3 years and using multiple linear regression data analysis techniques. The results of the study stated that firm size had no effect on capital structure, firm growth had no effect on capital structure and financial condition had no effect on capital structure. Company size, company growth and financial conditions have no simultaneous effect on capital structure in consumer goods industrial sector companies listed on the Indonesia Stock Exchange 2017-2019.